1993
DOI: 10.1093/jnci/85.5.388
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Taxol, Merbarone, and Piroxantrone in Stage IV Non-Small-Cell Lung Cancer: The Eastern Cooperative Oncology Group Results

Abstract: Further study of taxol is warranted. In future studies, taxol should be combined with other agents, and granulocyte colony-stimulating factor should be used to ameliorate myelosuppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
98
0
3

Year Published

1993
1993
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 325 publications
(104 citation statements)
references
References 0 publications
3
98
0
3
Order By: Relevance
“…Taxol has been found to be one of the most active drugs in patients with previously treated ovarian (Einzig et al, 1992;Rowinskly et al, 1992) and previously treated (Holmes et al, 1991;Nabholtz et al, 1993) or untreated (Seidman et al, 1992) breast carcinoma and with retained activity also in anthracycline-resistant breast carcinoma (Holmes et al, 1991;Seidman et al, 1993). In untreated advanced NSCLC, the response rate seems to be low, slightly above 20% (Chang et al, 1992;Murphy et al, 1993) and no responses were observed in 18 patients with advanced kidney carcinoma (Einzig et al, 1991).…”
Section: Discomsomentioning
confidence: 99%
“…Taxol has been found to be one of the most active drugs in patients with previously treated ovarian (Einzig et al, 1992;Rowinskly et al, 1992) and previously treated (Holmes et al, 1991;Nabholtz et al, 1993) or untreated (Seidman et al, 1992) breast carcinoma and with retained activity also in anthracycline-resistant breast carcinoma (Holmes et al, 1991;Seidman et al, 1993). In untreated advanced NSCLC, the response rate seems to be low, slightly above 20% (Chang et al, 1992;Murphy et al, 1993) and no responses were observed in 18 patients with advanced kidney carcinoma (Einzig et al, 1991).…”
Section: Discomsomentioning
confidence: 99%
“…Paclitaxel, a newer taxane, has been shown to be effective against a variety of cancers, including breast cancer (Holmes et al, 1991), ovarian cancer (Einzig et al, 1992), and lung cancer (Chang et al, 1993). Paclitaxel is also an effective drug for gastric cancer, with response rates ranging from 20 to 28% in single-agent phase II studies (Ajani et al, 1998;Ohtsu et al, 1998;Yamada et al, 2001;Yamaguchi et al, 2002).…”
mentioning
confidence: 99%
“…Clinical trials have demonstrated that paclitaxel is an active agent in the treatment of many cancers, e.g. epithelial and ovarian cancers (McGuire et al, 1989), breast cancers (Holmes et al, 1991) and lung cancers (Chang et al, 1993).…”
mentioning
confidence: 99%